User Interface Design for Web Collaborative Systems - Silva Filho, Antonio M. da; Barros, Roberto S. M. de; Liesenberg, Hans K. E. (Anais do Simpósio Brasileiro de Engenharia de Software (SBES), 2002)
Design for cooperation is a challenge. As designers we note that as we are getting into a new century, several areas have achieved significant breakthroughs. Among them, it is easy to perceive that Computing and Telecommunications have had an impact of paramount importance to society as a whole. These technologies have allowed an increasing integration of research fields, people of various backgrounds and abilities as well as made the interaction of different cultures possible. As a result, we have been living in the Internet era with a very large number of Web sites which can be visited, queried and played with. Application examples are Digital Libraries, Health Care Information Systems, Physics Collaboratories, and Web-based entertainments like interactive Web games. Within this context, we are concerned with the user interface design for such systems and a protagonist-oriented approach for capturing the user interface design is presented.